Prevalence and Risk Factors Associated with Carrying a Gun to School during Adolescence: A Statewide Study of Middle and High School Students. (2nd January 2020) - Docherty, Meagan; Sweeten, Gary; Craig, Tyleia; Yang, Vevette J. H.; Decrop, Romain; Beardslee, Jordan; Piquero, Alex; Clark, Catie; Pardini, Dustin
ABSTRACT: Although studies have identified risk factors for adolescent handgun carrying, previous research on risk factors for carrying a handgun to school specifically is sparse. This study examines self-report data from 122, 840 8th, 10th, and 12th grade students from 426 schools across Arizona, from three survey administrations (2014, 2016, and 2018). In each year, 0.5% to 0.8% of students reported carrying a handgun to school in the past year, and roughly half of the schools had at least one student who brought a gun to school. Multinomial logistic regression model results indicated that youth who carry a handgun to school are generally indistinguishable from non-school carriers; both kinds of carrying can be explained by risk factors related to criminal lifestyle, differential association, and fear of victimization theories. Findings suggest that programs aimed at reducing handgun carrying more generally might have an impact on carrying a gun to school.